Associations of Adipokine Levels With Levels of Remnant Cholesterol: The Multi‐Ethnic Study of Atherosclerosis - Renato Quispe; Ty Sweeney; Seth S. Martin; Steven R. Jones; Matthew A. Allison; Matthew J. Budoff; Chiadi E. Ndumele; Mohamed B. Elshazly; Erin D. Michos (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The metabolic syndrome phenotype of individuals with obesity is characterized by elevated levels of triglyceride‐rich lipoproteins and remnant particles, which have been shown to be significantly atherogenic. Understanding the association between adipokines, endogenous hormones produced by adipose tissue, and remnant cholesterol (RC) would give insight into the link between obesity and atherosclerotic cardiovascular disease. Methods and Results We studied 1791 MESA (Multi‐Ethnic Study of Atherosclerosis) participants who took part in an ancillary study on body composition with adipokine levels measured (leptin, adiponectin, and resistin) at either visit 2 or visit 3. RC was calculated as non–high‐density lipoprotein cholesterol minus low‐density lipoprotein cholesterol, measured at the same visit as the adipokines, as well as subsequent visits 4 through 6. Multivariable‐adjusted linear mixed‐effects models were used to assess the cross‐sectional and longitudinal associations between adipokines and log‐transformed levels of RC. Mean±SD age was 64.5±9.6 years; mean±SD body mass index was 29.9±5.0 kg/m2; and 52.0% were women. In fully adjusted cross‐sectional models that included body mass index, diabetes, low‐density lipoprotein cholesterol, and lipid‐lowering therapy, for each 1‐unit increment in adiponectin, there was 14.6% (95% CI, 12.2–16.9) lower RC. With each 1‐unit increment in leptin and resistin, there was 4.8% (95% CI, 2.7–7.0) and 4.0% (95% CI, 0.2–8.1) higher RC, respectively. Lower adiponectin and higher leptin were also associated with longitudinal increases in RC levels over median follow‐up of 5 (interquartile range, 4–8) years. Conclusions Lower adiponectin and higher leptin levels were independently associated with higher levels of RC at baseline and longitudinal RC increase, even after accounting for body mass index and low‐density lipoprotein cholesterol.